PENGEMBANGAN DESAIN PEMBELAJARAN TOPIK POLA BILANGAN BERBASIS REALISTIC MATHEMATICS EDUCATION (RME) DI KELAS VIII SMP/MTs - DEWI KARTIKA (Jurnal Edukasi dan Penelitian Matematika, 2018)
Abstract –The results of the preliminary study indicate that there are several problems in learning Number Pattern at Junior High School grade VIII. Although the example of pattern application was given in the daily live the teacher still has not designed the flow of the students learning by themselves. This research aimed to developing instructional design in topic the Number Pattern for Junior High School grade VIII with the Realistic Mathematic Education (RME) approach. This research is a kind of design research using Gravemeijer and Cobb model, which consists of three phases, namely the preparation phase for research (Preparation for the Experiment), experiment phase (Conducting the Experiment) and assessment phase (Retrospective Analysis). The subjects research were SMPN 4 Bukittinggi grade VIII. The results obtained that the conducting experiment stage indicate the problem is given in the activity series of students can stimulate the students to develop their knowledge and help them to find their own formulas in the material the Number Patterns. All of the strategies are used and discussed by the students that show how the students construct or contribute in finding the concept of Number Pattern from the informal level to the formal level. The result showed that the development of instructional learning design on numerical pattern topics based on realistic mathematic education in junior high school grade VIII was valid, practice and effective. The validity of this learning design is showed in the term of content and language. Practically seen in terms of implementation, ease and time needed in using a series of activities designed. Effective in term of its potential improve the students’ mathematical reasoning abilities. Keywords:Number Pattern,Instructional Design,Realistic Mathematics Education(RME), Design research